Regulation of Stem Cell Technology in Malaysia: Current Status and Recommendations - Gopalan, Nishakanthi; Nor, Siti Nurani Mohd; Mohamed, Mohd Salim (Science and engineering ethics, 2020)
Stem cell technology is an emerging science field; it is the unique regenerative ability of the pluripotent stem cell which scientists hope would be effective in treating various medical conditions. While it has gained significant advances in research, it is a sensitive subject involving human embryo destruction and human experimentation, which compel governments worldwide to ensure that the related procedures and experiments are conducted ethically. Based on face-to-face interviews with selected Malaysian ethicists, scientists and policymakers, the objectives and effectiveness of the current Guideline for Stem Cell Research and Therapy ( 2009 ) are examined. The study’s findings show that the guideline is rather ineffective in ensuring good ethical governance of the technology. A greater extent of unethical conduct is likely present in the private medical clinics or laboratories offering stem cell therapies compared with the public medical institutions providing similar services, as the latter are closely monitored by the governmental agencies enforcing the relevant policies and laws. To address concerns over malpractices or unethical conduct, this paper recommends a comprehensive revision of the current stem cell guideline so that adequate provisions exist to regulate the explicit practices of the private and public stem cell sectors, including false advertising and accountability. The newly revised Malaysian stem cell guideline will align with the Guidelines for Stem Cell Research and Clinical Translation ( 2016 ) of the International Society for Stem Cell Research (ISSCR) containing secular but universal moral rules. However, a regulatory policy formulated to govern the technology remains the main thrust of empowering the guideline for compliance among the stakeholders.